Analisis Strategi Pemasaran Produk Tabungan Emas di PT. Pegadaian Cabang Gunungsitoli (Jurnal Riset Manajemen dan Akuntansi, 2025)
The low participation of the public in utilizing the Gold Savings product at PT. Pegadaian Gunungsitoli Branch indicates a problem in the effectiveness of the marketing strategy implemented. A lack of financial literacy, minimal structured socialization activities, and limited promotional resources are the main factors hindering the increase of public interest in this product. These issues highlight the need for an in-depth study of the marketing approaches undertaken, the challenges faced in the field, and the solutions implemented as efforts to improve and enhance the effectiveness of a marketing strategy that is more adaptive to the needs of the local community. This research employs a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The results of the study show that the marketing strategy is carried out through direct education, utilization of social media, and consultative services to customers. However, the main challenges still relate to the public's limited understanding of gold investment and restricted digital access. In response to these challenges, Pegadaian Gunungsitoli has undertaken various initiatives, such as increasing educational activities, optimizing social media, and strengthening partnerships with community-based organizations. This research provides practical contributions to Pegadaian in improving its marketing strategy and theoretical implications in strengthening the marketing communication model of financial products based on local community engagement.